2022
DOI: 10.2147/cia.s363116
|View full text |Cite
|
Sign up to set email alerts
|

Level of LncRNA GAS5 and Hippocampal Volume are Associated with the Progression of Alzheimer’s Disease

Abstract: Purpose We evaluated the diagnostic value of long non-coding RNA growth arrest-specific transcript 5 (GAS5) and its relationship with hippocampal volume in Alzheimer’s disease (AD). Patients and Methods One hundred and eight patients with AD and 83 healthy controls were included, and demographic data, biochemical parameters, GAS5 levels, and hippocampal volume were recorded. Chi-squared tests or independent sample t-tests were used to compare the baseline characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Importantly, NPC86 binds to exon 12 which is highly conserved between mouse and human. Chen et al 71 analyzed PBMC from aged samples and reported that circulating GAS5 levels can be correlated to aging. We have shown that GAS5 is secreted in exosomes from cells, detected in serum and disease state can change the ratio of amount retained by cell versus secreted 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, NPC86 binds to exon 12 which is highly conserved between mouse and human. Chen et al 71 analyzed PBMC from aged samples and reported that circulating GAS5 levels can be correlated to aging. We have shown that GAS5 is secreted in exosomes from cells, detected in serum and disease state can change the ratio of amount retained by cell versus secreted 72 .…”
Section: Discussionmentioning
confidence: 99%
“…GAS5 is an anti-oncogene extensively studied in tumors [ 33 ]. Cao and colleagues found that silencing GAS5 improved functional recovery, suppressed neuron cell apoptosis, and inhibited the inflammatory response in HT22 cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that GAS5 may be associated with the progression of AD. Interestingly, the expression of GAS5 was negatively correlated with hippocampal volume, suggesting that GAS5 may play an important regulatory role in hippocampal atrophy [ 33 ]. In contrast, Khodayi et al did not find a significant difference in GAS5-AS expression in plasma cells of AD patients compared with healthy controls [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations